(untitled) (Swiss Medical Weekly, 2014)
BACKGROUND: Neonatal screening and treatment of phenylketonuria (PKU) prevent the development of neurocognitive impairment. The degree of dysfunction may be related to metabolic control and responsible for a hampered school career. METHODS: This was a retrospective study from a single metabolic unit of a Swiss University Hospital. The time point of diagnosis and all Phenylalanin (Phe) concentrations during the follow-up were recorded. The primary outcome was integration into professional life defined as no professional studies versus accomplished apprenticeship versus high school diploma/university. Phe levels were correlated with professional outcome. The control group consisted of the patients’ healthy parents and siblings. RESULTS: A total of 27 patients (13 females, 14 males) were included in the study. The mean (SD) follow-up period was 25.1 (7.6) years. The control group consisted of 57 subjects. Overall, 23 patients were diagnosed by neonatal screening, and 4 patients were diagnosed later. All 4 were in the non-professional study group. Compared with the controls there were significantly more patients in the non-professional study group (26% vs 9%, p <0.05) and significantly less in the accomplished apprenticeship group (59% vs 82%; p <0.04). After exclusion of the patients with late diagnosis no significant differences were found with regard to the professional integration between patients and controls. Significant differences in Phe-levels between the three groups could be documented between 2–10 years of age with the highest levels in the non-professional study followed by the accomplished apprenticeship and the high school diploma group (p <0.01). CONCLUSION: Patients who are diagnosed by neonatal screening and are consequently cared for are able to accomplish an apprenticeship or a high school diploma. Reference to electronic database: Phenylketonuria MIM # 261600